SISTEM INFORMASI AKUNTANSI LAPORAN ARUS KAS PADA BKM GABAHAN MAKMUR SEMARANG - Kasih Purwantini; Nonik Oktavia Saktiyani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2018)
This study aims to design an accounting information system for cash flow statements at BKM Gabahan Makmur Semarang. Through the creation of an Accounting Information System for Client Server Based Cash Flow Reports, it is expected to simplify the accounting section to record cash flow data, and to make balance sheets more quickly, which are used by BKM as a management tool for financial activities in BKM Gabahan Makmur Semarang. Where this system uses the Visual Basic 6.0 programming language, Crystal Report for the preparation of reports and Client Server-based, equipped with the distribution of access rights for each user. The research method used is the Borg and Gall R&D research approach which consists of 10 stages. Of the 10 stages of R&D the authors only approach the research up to the 6th stage alone. The results of the research of the accounting information system design of cash flow statements are to make it easier to record cash flows, and to make balance sheets more quickly compared to the manual system used at BKM Gabahan Makmur Semarang. Currently the BKM still uses a manual system in recording cash flow transactions, whereas by implementing an information system will minimize the risk of recording errors, so as to obtain information more quickly and completely.